Percutaneous laser photocoagulation of spinal osteoid osteomas under CT guidance. - Gangi, A; Dietemann, J L; Guth, S; Vinclair, L; Sibilia, J; Mortazavi, R; Steib, J P; Roy, C (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE Spinal osteoid osteomas are rare; when they occur, they are usually treated by surgical or percutaneous excision. The aim of percutaneous interstitial laser photocoagulation (ILP) of osteoid osteomas under CT guidance is thermal destruction of the nidus using low-power laser energy, thus precluding bone resection and open surgery.METHODS Three cases of spinal osteoid osteomas were treated with percutaneous ILP of the nidus. Under CT guidance, the needle was positioned in the center of the nidus, at least 8 mm from neurologic structures. Using a high-power semiconductor diode laser (805 nm) with a 400-microm optical fiber, we delivered 600 to 800 joules to the nidus, depending on its size. The procedure was performed with the patient under neuroleptanalgesia and required overnight hospitalization.RESULTS Complete pain relief was obtained in all three patients within 24 hours of the procedure, and no major complications were incurred. Follow-up ranged from 20 months to 60 months.CONCLUSION Percutaneous ILP of spinal osteoid osteoma is a promising, simple, precise, and minimally invasive technique and may be an alternative to traditional surgical and percutaneous ablations.